Bilateral Lymph Node Micrometastases and Seminal Vesicle Invasion Associated with Same Clinical Predictors in Localized Prostate Cancer. Issue 3 (May 2017) - Porcaro, Antonio B.; de Luyk, Nicolò; Corsi, Paolo; Sebben, Marco; Tafuri, Alessandro; Tamanini, Irene; Processali, Tania; Cerruto, Maria A.; Migliorini, Filippo; Brunelli, Matteo; Siracusano, Salvatore; Artibani, Walter
Aim: To determine clinical factors associated with multiple bilateral lymph node micrometastases and seminal vesicle invasion (pT3b) in organ-confined prostate cancer (PCa). Methods: The study excluded patients under androgen deprivation, with lymph node involvement (cN1 status), and having undergone unilateral pelvic lymph node dissection (PLND) during radical prostatectomy (RP). Lymph node micrometastases were classified as unilateral (pN1m) and bilateral (pN1b). Analysis considered multivariate multinomial logistic regression models. Results: Between January 2013 and March 2015, 140 patients underwent PLND during RP. Lymph node micrometastases were detected in 28 cases (20%) including pN1m in 19 (13.6%) and pN1b in 9 (6.4%). Independent clinical predictors of pN1b included prostate-specific antigen (PSA, µg/L) >12.5 (odds ratio [OR] = 43.0), proportion of positive biopsy cores (PBC) >0.57 (OR = 6.7), and biopsy Gleason grade (bGG) >3 (OR = 7.5). Independent pT3b predictors included PSA>12.5 (OR = 3.8), PBC>0.57 (OR = 4.1), and bGG>3 (OR = 3.8). Conclusions: In cN0 patients with localized PCa undergoing PLND, a nonnegligible rate of multiple lymph node micrometastases was detected (32.2%). In the natural history of PCa, there is a close association between pT3b and pN1b disease. Prostate cancer patients who are at high risk of extraglandular extension need selective pelvic staging by multiparametric magnetic resonance imaging to assess seminal vesicle invasion. Operated patients with pT3b and pNx status need close PSA monitoring because of the high probability of occult multiple bilateral lymph node micrometastases.